Rice productivity in Myanmar: Assessment of the 2022 dry season and farmers’ expectations for the monsoon of 2022 - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2022)
Rice is an extremely important product for farmers’ livelihoods and for food security in Myanmar. Rice is the main staple, accounting for 51 and 62 percent of urban and rural calories consumed, respectively, making it crucial for food security in the country.1 Large international changes in commodity markets and twin local crises – COVID-19 and political problems due to the military take-over – have raised doubts on the performance of the agricultural sector overall and the rice sector in particular. The assessment on farmers’ rice productivity during the dry season of 2022 presented in this research note is based on data from the Myanmar Agriculture Performance Survey (MAPS) that was conducted with 678 rice producers, spread over all states/regions of the country, over the period August 2022 – September 2022. Detailed questions were asked to farmers about their background, input use and input prices, farm management practices, rice output and output prices, and natural and other shocks during the dry season of 2021 and 2022.2 This research note presents the results from that assessment.